Pengembangan Sistem Informasi Point of Sales untuk Bengkel berbasis Cloud Computing (Studi Kasus: Bengkel Mas Pur Baturaja) - Bella Hersy Lavenia; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Bengkel Mas Pur Baturaja is a company that focuses on vehicle body repair services, especially for four-wheel vehicle. In the very beginning, Bengkel Mas Pur Baturaja uses manual data processing which requires that every transaction must be recorded. In this management, this company has many problem including unregistered transactions and incomplete transaction data. From these problems, a point of sales information system for car services shop was made. Point of sales information system for car services shop is a cloud computing-based system that can be accessed by users through a web browser, users will be easily to record every transaction by the company. The development of point of sales information systems for a workshops is using the CodeIgniter framework, a programming languages like PHP, HTML, CSS, Javascript and used MySQL as database. The implementation for cloud computing will be used Infrastructure service (IaaS) as service type that is AWS EC2 from Amazon Web Services as a cloud provider and the instance is t2.micro with Ubuntu Server 16.04 as operating system. Tests carried out on this system will use functional testing and non-fuctional testing. Functional testing on the system has 93% declared valid according to user requirements, and the system has been successfully run on several web browsers that are often generally used.